Sheesha Smoking Habits in Young Pakistani Female Students - Amena T. Rahim; Khadija I. Iqbal; Tehmina S. Qamar (Journal of King Abdulaziz University: Medical Sciences, 2023)
Sheesha smoking habit is found to be most prevalent in the 16-25 years age group with 70% sheesha smokers being male and 30% females. Alarming consequence is that either the customers or the people who serve it put addictive substances into it. The present study aims to assess the growing habits of sheesha smoking in Pakistani female students. Questionnaire was distributed among the girl students. Female students from different colleges/universities of Rawalpindi and Islamabad were included in the study. Statistics show that students offer each other the option to smoke sheesha, i.e., 51.6%. In this study's setting, 61.1% started sheesha smoking during their college life, and is considered fashionable by 68.1% and 54.9% are not aware of its harmful effects. Not much difference was seen between the parents about the awareness of their children sheesha smoking habit, i.e., 48.9% and 50.5%. 35.2% thought of it as losing weight tool and 22% to relieve depression. A large majority agreed that government should check this habit (78%). Government should get more actively involved against sheesha bars and to check for the banned substances. Study needs to be expanded to smaller cities.